Optimizing the Ability of Aceh Province in Paradiplomacy Practice - Novialdi, Risky; Rassanjani, Saddam (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2020)
This paper analyzes the opportunities for the development of Aceh province in the era of globalization. Paradiplomacy is one of the efforts that can be utilized to develop the Aceh province. Based on the Constitution Number 11 of 2006 on the Aceh government, has given Aceh province considerable authority to develop its territory, including establishing diplomatic relations with the regions others abroad through the Paradiplomacy practice. But, with this considerable authority, Aceh is still the poorest region in Sumatra and the poorest number 6 in Indonesia based on the statistics centre data (BPS) in 2019. This means that Aceh still fails to exploit its social and natural conditions for the development of its territory. In This research we used qualitative method, by gathering previous studies through observation, interviews and data collection. Aceh could utilize the